Penerapan Bentuk Perilaku Islami terhadap Kemampuan Perawat Mengimplementasi Asuhan Keperawatan Islami di Ruang Rawat Inap - Norman Alfiat Talibo; Tri Kurniati; Giri Widakdo (Journal of Telenursing (JOTING), 2019)
The purpose of this study is to determine the application of nurses' Islamic behavior to the ability to implement Islamic nursing care inpatients at the Sukapura Jakarta Islamic Hospital in 2019. This research method uses a quantitative approach with a Quasi-Experimental method with the research design is pre and post with control group design. Results The intervention group from the measurement before intervention was obtained a mean value of 82.53 and after intervention 98.68 at the measurement of week VI, with a difference of 16.15. While the average value in the control group between measurements before 75.34 and at the measurement of week VI obtained a mean value of 86.06 with a difference of 10.71. In conclusion, the application of Islamic behavior is effective in implementing Islamic nursing care at Sukapura Islamic Hospital, Jakarta in 2019. Keywords: Islamic Nursing Care, Islamic Nurse Behavior